Ability Matching and Survival of Start-Ups - Bettina Müller (Verein für Socialpolitik, 2010)
In this paper, I analyse how the survival of new firms is affected by the average ability level in the founding team, the team size, team members' homogeneity with respect to ability, and team members' heterogeneity with respect to education. As a theoretical basis, I apply the O-ring theory (Kremer (1993)). Using a rich employer-employee data set on the whole population of Danish firms founded in 1998, I find that the average ability level in a team and the team size have positive effects on firm survival. Having a team at all is the most crucial factor for the probability of survival of young firms. The degree of homogeneity with respect to ability and the degree of heterogeneity with respect to educations have no effect on the survival probability.
Keywords: D29; L23; M13; 330; entrepreneurship; firm survival; O-ring theory; start-ups